Thrombomodulin Mutations in Atypical Hemolytic–Uremic Syndrome - Delvaeye, Mieke; Noris, Marina; De Vriese, Astrid; Esmon, Charles T; Esmon, Naomi L; Ferrell, Gary; Del-Favero, Jurgen; Plaisance, Stephane; Claes, Bart; Lambrechts, Diether; Zoja, Carla; Remuzzi, Giuseppe; et al. (The New England journal of medicine, 2009)
Atypical hemolytic–uremic syndrome, a complex of microangiopathic hemolytic anemia, thrombocytopenia, and renal failure, is not associated with shigella toxin — unlike typical hemolytic–uremic syndrome — but is often associated with abnormal activation of complement by mutant components of the system. This study shows that in some patients with the atypical syndrome, there are disabling mutations of the THBD gene, which encodes thrombomodulin. As a result of these mutations, regulation of complement activation on cell surfaces is impaired, and cells are not protected from activated complement. This study shows that in some patients with the atypical hemolytic–uremic syndrome, there are disabling mutations of the THBD gene, which encodes thrombomodulin. As a result of these mutations, regulation of complement activation on cell surfaces is impaired, and cells are not protected from activated complement. The hemolytic–uremic syndrome consists of the triad of microangiopathic hemolytic anemia, thrombocytopenia, and acute renal failure. It is one of the thrombotic microangiopathies, along with thrombotic thrombocytopenia purpura and preeclampsia. 1 The hemolytic–uremic syndrome is the most common cause of acute renal failure among children, a condition for which 50 to 75% of patients require dialysis. 2 More than 85% of cases of the hemolytic–uremic syndrome are referred to as “typical”; these are preceded by diarrhea caused by strains of Escherichia coli 3 – 5 that produce Shiga-like toxins, which have proinflammatory and prothrombotic effects on the vascular endothelium. 6 Most cases of typical hemolytic–uremic . . .